Current Research Developments on the Processing and Improvement of the Nutritional Quality of Rapeseed (Brassica napus L.). Issue 5 (18th March 2019) - Beszterda, Monika; Nogala‐Kałucka, Małgorzata
Abstract : Brassica napus is cultivated largely as a winter or semi‐winter form in Europe and Asia, respectively, whereas spring‐sown rape types are more adapted to the climatic conditions in Canada, northern Europe, and Australia. This plant, the third most important oil crop in the world after maize and oil palm, has had a unique history among those crops that have been targets of breeding and genetic modification. Although agronomy and genetic manipulations of B. napus plants to create seed with substantially no erucic acid content in the seed oil and meal largely free from aliphatic glucosinolates were major breakthroughs, opportunities for further advances in the reduction of antinutritive compounds/enhancement of bioactive compounds, in oil and meal health safety and quality, as well as in agronomic performance and pest resistance, are still greater today than they have ever been. Understanding and application of genetic control for key agronomic traits in B. napus, such as seed oil composition and concentration as well as their environmental interactions, are the main targets, which will underpin the development of the crop for cultivation in an extensive range of environments. It is also needed to improve phytochemical content through traditional breeding programs or through bioengineering of the phenylpropanoid pathway, leading to desirable secondary metabolite accumulation. This paper is a review of modifications (in the field of biotechnology, agronomy, and processing) that have been applied to improve the nutritional value of B. napus L. Practical Applications : This paper has value for people starting their scientific work in the field related to the B. napus biotechnology and nutritional value of vegetable oils. In addition, it is a current compedium of knowledge for people working professionally in the oil industry. Moreover, this article is a cross‐section of the current achievements of genetic engineering in improving the composition of rapeseed and indicates key publications on this subject. Brassica napus L., the third most important oil crop in the world after maize and oil palm, has a unique history among those crops that are targets of breeding and genetic modification. Effective tools of processing, biotechnology, and agronomy are essential to produce rapeseed oil with a high amount of bioactive compounds and continue to be employed in strengthening the product versatility. Abstract : Brassica napus L., the third most important oil crop in the world after maize and oil palm, has a unique history among those crops that are targets of breeding and genetic modification. Effective tools of processing, biotechnology, and agronomy are essential to produce rapeseed oil with a high amount of bioactive compounds and continue to be employed in strengthening the product versatility.